The development of problem solving young children a critical cognitive skill. [article]. - Keen, Rachel
Problem solving is a signature attitude of adult humans, but we nee to understand how this develops in children. Tool use is proposed as an ideal way to study problem solving in children less than 3 years of age because overt manual action can reveal how the child plans to achieve a goal. Motor errors are as informative as successful actions. Research is reviewed on intentional actions, beginning with block play and progressing to picking up a spoon in different orientations, and finally retrieving objects with rakes and from inside tubes. Behavioral and kinematic measures of motor action are combined to show different facts of skill acquisition and mastery. We need to design environments that encourage and enhance problem solving from a young age. One goal of this review is to excite interest and spur new research on the beginnings of problem solving and its elaboration during development. - (from the author)